Conservation of imprinting of MKRN3 and NAP1L5 in rabbits. (19th April 2016) - Yuan, L.; Lai, L.; Duan, F.; Chen, M.; Deng, J.; Li, Z.
Summary: Maternally imprinted genes of makorin ring finger protein 3 ( MKRN3 ) and nucleosome assembly protein 1‐like 5 ( NAP1L5 ) have been identified in many species but have not yet been investigated in rabbits. In this study, a polymorphism‐based approach and bisulfite‐sequencing PCR (BSP) were used to determine the imprinting status of MKRN3 and NAP1L5 in rabbits. The single nucleotide polymorphism (SNP)‐based sequencing results demonstrated that MKRN3 and NAP1L5 were expressed preferentially from the paternal allele. Furthermore, the BSP results showed the gamete‐specific methylation patterns and hemimethylation in brain and full methylation in liver were observed in MKRN3 and NAP1L5 respectively. Thus, we provide the first evidence that MKRN3 and NAP1L5 are paternally expressed genes and that the CpG islands located in the promoter region may be the putative differentially methylated region of these two genes in rabbits.